2008
DOI: 10.1111/j.1600-0722.2007.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary trefoil factor 3 enhances migration of oral keratinocytes

Abstract: Trefoil factor 3 (TFF3) is a member of the mammalian TFF family. Trefoil factors are secreted onto mucosal surfaces of the entire body and exert different effects according to tissue location. Trefoil factors may enhance mucosal healing by modulating motogenic activity, inhibiting apoptosis, and promoting angiogenesis. Trefoil factor 3 is secreted from the submandibular gland and is present in whole saliva. The aim of this study was to assess the migratory and proliferative effects of TFF3 on primary oral huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 35 publications
4
47
0
2
Order By: Relevance
“…ITF have been reported to promote cell proliferation and migration of epithelial cells in some studies (7,17,18), and our experiments indicated that ITF promote proliferation and migration of GES-1 cell in vitro. To verify whether Akt signaling pathway participated in this stimulatory effect, CCK-8 assays and transwell migration assays were performed.…”
Section: Activated Akt Signaling Is Required For Itf-induced Ges-1 Cesupporting
confidence: 49%
“…ITF have been reported to promote cell proliferation and migration of epithelial cells in some studies (7,17,18), and our experiments indicated that ITF promote proliferation and migration of GES-1 cell in vitro. To verify whether Akt signaling pathway participated in this stimulatory effect, CCK-8 assays and transwell migration assays were performed.…”
Section: Activated Akt Signaling Is Required For Itf-induced Ges-1 Cesupporting
confidence: 49%
“…That these effects could reversed by a β-AR antagonist, but not an α 2 -AR-antagonist, suggests that the migratory effects are mediated by the β-AR, and since the β 2 -AR is the only β-AR expressed, it is likely that the effects are mediated by the β 2 -AR. The catecholamine agonists also decrease the activity of the pro-migratory ERK and p38 MAPK, kinases required for epithelial cell migration (McCawley et al, 1999;Fitsialos et al, 2007;Storesund et al, 2008;Shi et al, 2009;Sivamani et al, 2009b) and convert HOK from a migratory to a stationary phenotype. Additionally, the HOK themselves can generate catecholamine ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The TFF3 protein also activates STAT3 signaling in human colorectal cancer cells, thus providing cells with invasion potential (20). TFF3 treatment leads to EGF receptor activation and ␤-catenin phosphoryla-tion in HT-29 cells (21) and to transient phosphorylation of ERK1/2 in oral keratinocytes (22). With respect to TFF2, recombinant peptide enhances the migration of human bronchial epithelial cell line BEAS-2B (4).…”
mentioning
confidence: 99%